The prevalence of Stevens Johnson Syndrome caused by antiretroviral in hospitalized patients at Dr. Hasan Sadikin General Hospital Bandung - Maelani, Nurmilah; Sufiawati, Irna; Darmadji, Hartati Purbo (Padjadjaran Journal of Dentistry, 2009)
Stevens-Johnson Syndrome is a mucocutaneous disease caused by allergic drug eruption. Antiretroviral (ARV) therapy for HIV/AIDS patient may cause allergic drug eruption such as Stevens-Johnson Syndrome.The aim of this research was to find out the prevalence of Stevens-Johnson Syndrome caused by ARV in hospitalize patient at Dr.Hasan Sadikin General Hospital Bandung from January to December 2008.It was a descriptive research by taking the secondary data from patient’s medical record. The result of this research showed that from 20 Stevens-Johnson Syndrome patients, 12 persons of them (60%) are men.Most of the patients were between the age of 20-29 (45%).Oral manifestation of Stevens-Johnson Syndrome seen in 100% patients.Prevalence of Stevens-Johnson Syndrome caused by ARV was 28.6% which seen in 8 HIV/AIDS patients.ARV combination consists of nevirapine, lamivudine, and zidovudine was the most (50.0%) ARV which suspected causing Stevens-Johnson Syndrome.The conclusion of this research showed that the prevalence of Stevens-Johnson Syndrome caused by ARV in hospitalize patient at Dr.Hasan Sadikin General Hospital Bandung 2008 was 28.6% seen in 8 HIV/AIDS patients.